MAPPING SETTLEMENT QUALITY AND HEALTH CONDITION IN COASTAL AREA OF JEPARA DISTRICT 2019 - Rido Feisal; Yasin Yusup; Rita Noviani (Universitas Sebelas Maret (UNS), 2020)
The research Purposes is 1) Knowing coastal settlement quality at jepara district 2) Knowing coastal health condition level society 3) Knowing the correlation settlement quality between health level condition at Jepara District. The method used in this research is descriptive quantitative with spatial approach, the population in this research is settlement located at coastal area of Jepara District in 5 villages Demaan, Bulu, Kauman, Jobokuto, Ujungbatu. Technical sampling used proportional random sampling. Based on the result of the research the conclusion of the research is (1) settlement quality in coastal is on the good classified and medium classified for 34 settlement block which proportion 8 block is good classified and 26 block medium classified. The methode used is sattelite images interpretation and terrestrial. (2) health level condition in coastal has a various level from high classified and low classified if it is seen from incident rate of 5 diseases, based on administration demaan has the IR of 13,03 (low), Bulu 25,16 (high), Kauman 16,37 (low), Jobokuto 19,35 (normal), Ujungbatu 18,05 (normal) it shows that Demaan village has IR 13,03 it means there are 13 people which has illness out of 100. (3) correlation between settlement quality and health level condition in coastal has same direction but not too significant, with correlation value 0,275 (enough). correlation health level condition not only caused from settlement quality but it caused by many factor in that area.